Pelatihan Pembuatan dan Penggunaan Website E-Commerce Bagi Wirausaha Pemula di Kota Jayapura - Yasir Attamimi; Chrisostommi Wirayudha Tuhumena; Alfa Mesak Suebu (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Since the Corona Virus Disease 2019 (COVID-19) attack, Indonesian consumer habits have rapidly developed into a different model than before, where people are now more accustomed to carrying out various types of activities such as studying, working, shopping and others only from home by utilizing various digital features so they don't have to go out of the house. The purpose of conducting this training and service is to increase the competence of novice entrepreneurs in creating e-commerce websites for novice entrepreneurs, especially in Jayapura City and also as an understanding and at the same time improving quality in the IT field for novice entrepreneurs, especially in Jayapura City. The method in this training and service uses four stages, namely: (1) preparation (2) coordination (3) training and (4) evaluation and strengthening. The results and achievements obtained are (1) training on creating and using e-commerce websites for novice entrepreneurs in Jayapura City is very important to convey because most trainees who are novice entrepreneurs admit that using e-commerce websites will really help them in carrying out their buying and selling activities in the future. (2) This training also improves technology mastery among novice entrepreneurs so that it can have a positive impact.Keywords : Training, E-Commerce